2019
DOI: 10.1089/dia.2019.0070
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Directions for Electronic Point-of-Care Clinical Decision Support to Improve Diabetes Management in Primary Care

Abstract: In the past decade there have been major improvements in the design, use, and effectiveness of point-of-care clinical decision support (CDS) systems to improve quality of care for patients with diabetes and related conditions. Advances in data exchange, data security, and human factors research have driven these improvements. Current diabetes CDS systems have high use rates, high clinician/user satisfaction rates, and have measurably improved glucose control, blood pressure control, and cardiovascular risk tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In this supplement, O'Connor and Sperl-Hillen present a comprehensive review of how advancements in data exchange, data security, and human factors research have improved the design and effectiveness of point-of-care clinical decision support (CDS) systems in primary care setting. 19 Emerging data provide compelling evidence that current diabetes CDS systems have high rates of usage and have improved glycemic control, blood pressure control, and cardiovascular risk trajectories in adults with diabetes. CDS systems both personalize care to reflect individual patient needs and standardize recommendations, thus reducing undesirable variation in care.…”
mentioning
confidence: 99%
“…In this supplement, O'Connor and Sperl-Hillen present a comprehensive review of how advancements in data exchange, data security, and human factors research have improved the design and effectiveness of point-of-care clinical decision support (CDS) systems in primary care setting. 19 Emerging data provide compelling evidence that current diabetes CDS systems have high rates of usage and have improved glycemic control, blood pressure control, and cardiovascular risk trajectories in adults with diabetes. CDS systems both personalize care to reflect individual patient needs and standardize recommendations, thus reducing undesirable variation in care.…”
mentioning
confidence: 99%
“…It is possible that the EBMeDS system alone was not a sufficiently intensive approach. Multifaceted strategies, such as CCDS systems in combination with continuing education and feedback mechanisms, are probably more appropriate in Belgian family medicine at the moment [36,37]. Studies have already demonstrated the benefits of adding patient-oriented strategies to decision support [12,[38][39][40].…”
Section: Interpretation Of Main Resultsmentioning
confidence: 99%
“…SDM is a process for clinicians, patients, and caregivers to partner in the development of the most appropriate and feasible therapeutic plan at a given time based on expert input from both the clinician (grounded in the best available scientific evidence) and the patient/caregiver (providing expertise in the patient’s goals, preferences, and context of care) 132. SDM is facilitated by decision aids for diabetes management,133 conversational elicitation of the patient’s goals/preferences,134 and/or integrated, holistic clinical decision support tools 135136137. Use of decision aids, in particular, allows therapeutic goals and treatment options to be discussed and considered in the context of the patient’s preferences.…”
Section: Models Of Carementioning
confidence: 99%
“…138 This decision aid has been used in a variety of clinical contexts, and trials have shown that decision aids can effectively and efficiently facilitate SDM without increasing the burden on clinicians or systems 139. Decision support tools can also be designed to be holistic (that is, not focused on glycemic reduction alone) and adapted to facilitate and inform evidence based SDM,135140 particularly in primary care where most people with type 2 diabetes receive their care.…”
Section: Models Of Carementioning
confidence: 99%
See 1 more Smart Citation